Online Transactions in the Long-Term Insurance Industry - Gouws, Daniel (Department of Commercial Law, 2014)
This paper will endeavour to consider the extent to which our legal system currently makes it possible for transactions to be concluded electronically within the long-term insurance and financial services industry.